No se está quieto : nuevas formas documentales en el audiovisual hispánico - Álvarez, Marta; Sánchez Alarcón, Inmaculada; Hatzmann, Hanna (Aproximaciones a las culturas hispánicas, 2015)
Documentary film has at the beginning of the new century experienced a great revaluation and commercial boom. This volume examines the circumstances that led to the boom in the Hispanic context and features the variety that exist within documentary forms - from those produced by organizations and individual filmmakers, to those developed on the Internet or born in the museum. It also gives voice to some indispensable artists of today.